Nematode Management in Organic Agriculture - Zane Joseph Grabau; Robert McSorley (EDIS)
The objectives of this publication are to provide information on plant parasitic nematodes causing damage in organic agriculture and to introduce methods for their management. The intended audience is agricultural professionals and anyone producing agricultural products organically.